Phylogenetic analysis of endogenous viral elements in the rice genome reveals local chromosomal evolution in Oryza AA-genome species - Saito, Nozomi; Chen, Sunlu; Kitajima, Katsuya; Zhou, Zhitong; Koide, Yohei; Encabo, Jaymee R.; Diaz, Maria Genaleen Q.; Choi, Il-Ryong; Koyanagi, Kanako O.; Kishima, Yuji (Frontiers in plant science, 2023)
Rice genomes contain endogenous viral elements homologous to rice tungro bacilliform virus (RTBV) from the pararetrovirus family . These viral elements, known as endogenous RTBV-like sequences (eRTBVLs), comprise five subfamilies, eRTBVL-A, -B, -C, -D, and -X. Four subfamilies (A, B, C, and X) are present to a limited degree in the genomes of the Asian cultivated rice (spp. and ) and the closely related wild species . The eRTBVL-D sequences are widely distributed within these and other AA-genome species. Fifteen eRTBVL-D segments identified in the (Nipponbare) genome occur mostly at orthologous chromosomal positions in other AA-genome species. The eRTBVL-D sequences were inserted into the genomes just before speciation of the AA-genome species. Ten eRTBVL-D segments are located at six loci, which were used for our evolutionary analyses during the speciation of the AA-genome species. The degree of genetic differentiation varied among the eRTBVL-D segments. Of the six loci, three showed phylogenetic trees consistent with the standard speciation pattern (SSP) of the AA-genome species (Type A), and the other three represented phylogenies different from the SSP (Type B). The atypical phylogenetic trees for the Type B loci revealed chromosome region-specific evolution among the AA-genome species that is associated with phylogenetic incongruences: complex genome rearrangements between eRTBVL-D segments, an introgression between the distant species, and low genetic diversity of a shared eRTBVL-D segment. Using eRTBVL-D as an indicator, this study revealed the phylogenetic incongruence of local chromosomal regions with different topologies that developed during speciation.